LOESS FORMATION IN THE LIGHT OF RECENT PALEOMAGNETIC DATA (GLOBAL REVIEW) - Moszherin V.V. (My University, 1999)
Loess rocks are widespread on the Earth. They occupy about 10% of global land area. Their thickness reaches up to 300 m in places and even more. Loess rocks differ in the different parts of the Earth. The 'warm' and the 'cold' loess rocks may be distinguished. They differ not only by conditions of their formation: the 'warm' loess rocks are older. The age of oldest loess according to magnetostratiraphic data is about 3.5 My. The accumulation rate of fine earth was estimated by paleomagnetic dating. Paleomagnetic method gives manifold possibilities for paleoclimate reconstructions.